The influence of the duration of led lighting on the biochemical composition of the peas microgreens - Pashkevich, Hanna M.; Tchaikovsky, Andrey I.; Rupasova, Zhanna A.; Vasilevskaya, Tamara I.; Krinitckaya, Natalya B. (Journal of the Belarusian State University. Ecology, 2022)
The results of a comparative study of the effect of the duration of LED lighting are presented (8, 10, 12, 14, 16 hour) on 13 characteristics of the biochemical composition of vegetable peas microgreens (Pavlusha variety) - the content of dry, tannic and pectin substances, free organic, ascorbic and hydroxycinnamic acids, soluble sugars, total protein and albumins, the main groups of bioflavonoids and the indicator of the sugar acid index.The dry matter content in the studied samples was 9.3-11.8 %, the content of free organic, ascorbic and hydroxycinnamic acids in the dry mass was 4.35-8.46 %, 359.8-487.8 mg/100 g and 1465.1-1956.0 mg/100 g, respectively. The content of soluble sugars was from 8.8 to 13.2 % with significant variant differences in the indicator of the sugar acid index, which varied in the range of 1.04-3.03. At the same time, the parameters of the accumulation of pectin substances were 3.884.54 %, the content of tannins - 1.23-1.92 %. The almost complete absence of anthocyanin pigments in the pea microgreens was found, the content of flavonols varied in the range of 1711.7-2189.2 mg/100 g, and catechins - 376.7-483.0 mg/100 g. At the same time, a high content of proteins and their valuable part - soluble proteins (albumins), which varied in mg/g of dry weight in the ranges of 412.3-443.4 and 8.38-18.0, was found in the microgreens.The considerable width of the ranges of variation of the biochemical characteristics of the micro-green peas testified to their significant dependence on the duration of LED lighting, which was ambiguous. The least significant changes in the biochemical composition of peas microgreens relative to the control (12 hours duration) were detected at 10 and 14 hours of illumination duration, while the greatest - at 8 and especially at 16 hours duration. At the same time, the highest integral level of nutritional and vitamin value of products according to the totality of biochemical characteristics is set at 14 hours of illumination, while the minimum is at 8 hours.
Keywords: duration of LED lighting; peas; micro-greens; biochemical composition; organic acids; carbohydrates; proteins; bioflavonoids; nutritional and vitamin value of products